Multiomics Analysis Reveals Molecular Abnormalities in Granulosa Cells of Women With Polycystic Ovary Syndrome - Zhao, Rusong; Jiang, Yonghui; Zhao, Shigang; Zhao, Han (Frontiers in Genetics, 2021)
Polycystic ovary syndrome (PCOS) is the most common complex endocrine and metabolic disease in women of reproductive age. It is characterized by anovulatory infertility, hormone disorders, and polycystic ovarian morphology. Regarding the importance of granulosa cells (GCs) in the pathogenesis of PCOS, few studies have investigated the etiology at a single “omics” level, such as with an mRNA expression array or methylation profiling assay, but this can provide only limited insights into the biological mechanisms. Here, genome-wide DNA methylation together with lncRNA-miRNA-mRNA profiles were simultaneously detected in GCs of PCOS cases and controls. A total of 3579 lncRNAs, 49 miRNAs, 669 mRNAs, and 890 differentially methylated regions (DMR)-associated genes were differentially expressed between PCOS cases and controls. Pathway analysis indicated that these differentially expressed genes were commonly associated with steroid biosynthesis and metabolism-related signaling, such as glycolysis/gluconeogenesis. In addition, we constructed ceRNA networks and identified some known ceRNA axes, such as lncRNAs-miR-628-5p-CYP11A1/HSD17B7. We also identified many new ceRNA axes, such as lncRNAs-miR-483-5p-GOT2. Interestingly, most ceRNA axes were also closely related to steroid biosynthesis and metabolic pathways. These findings suggest that it is important to systematically consider the role of reproductive and metabolic genes in the pathogenesis of PCOS.